STRATEGIC BUSINESS TRANSFORMATION AND CORPORATE SUSTAINABILITY: EXAMINING THE ROLE OF DYNAMIC AND DIGITAL CAPABILITIES - Situmorang, Patar; Purba, John Tampil; Hariandja, Evo Sampetua (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2025)
In today's dynamic and competitive business environment, organizations must continuously adapt to external and internal changes to achieve corporate sustainability. This study examines the influence of Business Transformation (BT), Service Innovation Capability (SIC), and Service Delivery (SD) on Corporate Sustainability (CS), with Dynamic Capability (DC) as a mediating variable and Digital Transformation (DT) as a moderate factor. Employing Resource-Based View (RBV) and Market-Based View (MBV) theories, this study aims to explore how firms leverage internal capabilities and external market factors to drive long-term sustainability. A quantitative research design was applied, utilizing